RELATIONSHIP BETWEEN OBESITY, TWIN-PREGNANCY AND PREVIOUS HISTORY OF PREECLAMPSIA WITH PREECLAMPSIA - Riani Widia Parantika; Gatut Hardianto; Muhammad Miftahussurur; Wahyul Anis (UNIVERSITAS AIRLANGGA, 2021)
Background: Preeclampsia can threaten the health of the mother and fetus during pregnancy and childbirth, besides that it also increases the risk of long-term complications and has the potential to cause death. The incidence of preeclampsia at the RSUD Engku Haji Daud Tanjung Uban showed an increase in the last three years, namely the occurrence from 2017 as many as 23 cases to 56 cases in 2019. The condition of preeclampsia can worsen quickly and without warning, for that, it must be detected and managed appropriately. This study aimed to identify the association of obesity, multiple pregnancies, and previous history of preeclampsia with the incidence of preeclampsia in maternity women. Methods: This study uses a case-control study design. Performed on women giving birth in the period January – December 2019, consisting of 56 cases and 112 controls. Maternal women with preeclampsia were cases and women who were not diagnosed with preeclampsia were controls. The data was obtained from the respondents' medical records, then analyzed using the Chi-Square test or Fisher's Exact test with a value of = 0,05. Results: Obesity was associated with an increased risk of preeclampsia (OR= 4,746, 95% CI 2,381-9,460; P=0,000). Multiple pregnancies were associated with a significantly increased risk of preeclampsia (OR=15,857, 95% CI 1,899-132,384; P=0,002). Likewise, a previous history of preeclampsia was associated with a markedly increased risk of preeclampsia (OR=99,000, 95% CI 22,057-444,343; P=0,000). Conclusion: Based on these data, it was found that obesity, multiple pregnancies, and previous history of preeclampsia were significant risk factors for the occurrence of preeclampsia. It is important to identify risk factors for preeclampsia early, so that appropriate management can be carried out, to prevent complications.